Initiation of safflower sowings in the organic farming system of Western Kazakhstan - Nasiyev, B.; Bushnev, A.; Zhanatalapov, N.; Bekkaliyev, A.; Zhylkybay, A.; Vassilina, T.; Shibaikin, V.; Tuktarov, R. (OCL-OILSEEDS AND FATS CROPS AND LIPIDS, 2022)
We carried out the research in 2020-2021 in Western Kazakhstan on medium-loamy dark chestnut soils. The purpose of the research is to identify changes in physico-chemical, biological parameters of soil cover, productivity, and quality of safflower (Carthamus tincforius L.) under the influence of different technologies of agrarian landscape shaping, for rational management of organic agrocenoses. The field experiments showed that in the conditions of Western Kazakhstan, the use of the biologized technology of organic farming increases the yield of safflower in comparison with the traditional technology by 26.66-35.38%, with a high oil content of 30.0-39.95%. The phytoameliorative role of safflower in improving agrophysical, agrochemical, and biological parameters of dark chestnut soils is proved.Исследования проводились в 2020-2021 годах в Западном Казахстане на среднесуглинистых темно-каштановых почвах. Цель исследований - выявить изменения физико-химических, биологических показателей почвенного покрова, продуктивности и качества сафлора красильного (Carthamus tincforius L.) под влиянием различных технологий агроландшафтного формирования, для рационального управления органическими агроценозами. Полевые опыты показали, что в условиях Западного Казахстана применение биологизированной технологии органического земледелия повышает урожайность сафлора по сравнению с традиционной технологией на 26,66-35,38 %, при высоком масличности 30,0-39,95 %. Доказана фитомелиоративная роль сафлора в улучшении агрофизических, агрохимических и биологических показателей темно-каштановых почв.
Keywords: импакт-фактор 2022; кларивате аналитикс; web of science; дальнее зарубежье; научный журнал; периодическое издание; масличные культуры; сафлор; сафлор красильный